The Engineering Potential of Rhodosporidium toruloides as a Workhorse for Biotechnological Applications - Park, Young-Kyoung; Nicaud, Jean-Marc; Ledesma-Amaro, Rodrigo (Trends in biotechnology (Regular ed.), 2018)
Moving our society towards a bioeconomy requires efficient and sustainable microbial production of chemicals and fuels. Rhodotorula (Rhodosporidium) toruloides is a yeast that naturally synthesizes substantial amounts of specialty chemicals and has been recently engineered to (i) enhance its natural production of lipids and carotenoids, and (ii) produce novel industrially relevant compounds. The use of R. toruloides by companies and research groups has exponentially increased in recent years as a result of recent improvements in genetic engineering techniques and the availability of multiomics information on its genome and metabolism. This review focuses on recent engineering approaches in R. toruloides for bioproduction and explores its potential as a biotechnological chassis. Finding the right microorganism is a key issue for a bioprocess. Ideally, it should be a good natural producer, use low-cost substrates, and perform well at large scale. An engineering process is often required to satisfy such requirements. Lipids and carotenoids are two industrially relevant compounds. Lipids are a good source of fuels and chemicals which could facilitate the replacement of petroleum. Carotenoids are used as ingredients for the food, feed, pharma, and cosmetic industries. R. toruloides naturally synthesize high amounts of these compounds, which makes it a good candidate for their production. R. toruloides has recently emerged as one of the most promising yeasts for bioproduction. In addition to its natural and convenient industrial features, it can now be metabolically engineered to boost production levels and to expand the range of compounds that are produced.